Menyemai Ilmu Dan Kompetensi Pedagogik 4.0 Oleh Guru Pendidikan Agama Kristen - Sensius Amon Karlau; Ivo Sastri Rukua (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
Efforts to sow knowledge and pedagogic competencies for PAK teachers in the era of the industrial revolution 4.0 are positive breakthroughs for the effectiveness of PAK learning in facing various educational challenges and problems. The method used is qualitative, accompanied by a literature study approach. Text analysis and thinking through various literatures that discuss pedagogic science, pedagogic competence, the role of PAK teachers, and the industrial era 4.0 are used carefully. The results obtained show that pedagogic science, according to the continental and pragmatic views in an integrative manner, has individual, personal, moral and social relations motives that lead to pedagogic competence 4.0. This has implications for the realization of educational and learning processes by PAK teachers that are relevant in the industrial era 4.0. So it was concluded that PAK teachers need pedagogic knowledge as a stimulant that enhances pedagogic competence 4.0 which includes their role as educators, instructors and mentors supported by the use of information technology devices or media proportionally for the effectiveness of PAK learning in the industrial era 4.0.